Clinical application of the parathyroid implant - Cazabán, Luis A; del Campo, Alberto; Servetti, Eduardo; Gómez Fossati, Carlos; Crestanello, Francisco (Cirugía del Uruguay, 1972)
The purpose of parathyroid gland implants is to provide a constant endogenous source of hormone, implant seeking a definitive solution to parathyroprive tetany.